Secukinumab May Be an Effective Treatment Option for Axial Spondyloarthritis and Psoriatic Arthritis Patients with a History of Malignancy: Multicenter Real-Life Experience from Turkey - Ocak, Tugba; Yagiz, Burcu; Ocak, Birol; Yogurtcu, Ozge; Basibuyuk, Fatma; Tezcan, Dilek; Pehlivan, Yavuz (Mdpi, 2024)
Background: Secukinumab is a monoclonal antibody against interleukin 17 approved for patients with axial spondyloarthritis (axSpA), psoriatic arthritis (PsA), and psoriasis. Treating axSpA and PsA patients with a history of malignancy is a challenge. While initial results on the applicability of secukinumab in this patient group are positive, the number of studies on this topic remains limited. This study aimed to investigate the drug's survival time and the efficacy and safety of secukinumab treatment in this specific patient group. Methods: This retrospective study included 30 patients with a history of malignancy who were followed up in rheumatology outpatient clinics in 12 centers throughout Turkey and treated with secukinumab between May 2018 and March 2024 with a diagnosis of axSpA and PsA. Results: The mean follow-up time was 29.8 +/- 19.3 months. The drug retention rate was 89.7% after 12 months and 80.6% after 24 months. The most common tumor in our study was papillary thyroid carcinoma (n = 5, 16.7%). During follow-up, local tumor recurrence was observed in a patient with urothelial carcinoma of the bladder. Conclusions: In the largest cohort reported to date, treatment with secukinumab in axSpA and PsA patients with a history of malignancy was not shown to cause oncologic recurrence except for one local tumor recurrence. Drug retention rates were also high, and disease activation and function improved compared to baseline. Therefore, secukinumab could be a safe and effective option for this patient group.
Keywords: axial spondyloarthritis; psoriatic arthritis; malignancy; secukinumab